1992
DOI: 10.1111/j.1550-7408.1992.tb01467.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acanthamoeba at the Generic and Specific Levels Using the Polymerase Chain Reaction

Abstract: We have adapted the polymerase chain reaction to identify strains of Acanthamoeba. Using computer-assisted analysis, primers were designed from an anonymous repetitive sequence and from published sequences of 18S and 5S ribosomal RNA genes of A. castellanii. Amplification of a short ribosomal DNA target (272 base pairs) at restrictive annealing conditions (greater than 50 degrees C) resulted in a single band that was unique for the genus and distinguished Acanthamoeba from Naegleria. This assay functioned with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 25 publications
2
47
0
2
Order By: Relevance
“…JDP2 is a modification of ACARNA. 1383 (40) and RGPG (11). The JDP1-JDP2 primer pair previously was shown at OSU to produce the amplimer now designated ASA.S1 from acanthamoebae isolated from tissues of freshwater fishes (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…JDP2 is a modification of ACARNA. 1383 (40) and RGPG (11). The JDP1-JDP2 primer pair previously was shown at OSU to produce the amplimer now designated ASA.S1 from acanthamoebae isolated from tissues of freshwater fishes (10).…”
Section: Methodsmentioning
confidence: 99%
“…The identification of amoebic isolates should be very reliable and, at least for clinical use, the detection system should be very sensitive. Several research groups, including our own, have demonstrated the usefulness of PCR methods for detection of acanthamoebae (10,15,21,25,27,40). As few as 1 to 10 trophozoites can be detected.…”
mentioning
confidence: 99%
“…Approaches that have been useful include RFLP analysis of the entire mitochondrial genome, 12,20-25 riboprinting (described below) of 18S rDNA, 12,26 production of typespecific PCR amplimers, [27][28][29][30] analyses based on sequences of subgenic PCR amplimers [30][31][32] as well as the development of fluorescent oligonucleotide probes for in situ staining that are specific either for the genus Acanthamoeba or for genotype T4. 33 The recent introduction of a 'reverse dot-blot' technique holds promise for the eventual simultaneous detection and identification of all rDNA genotypes present in any specimen.…”
Section: Molecular Epidemiologymentioning
confidence: 99%
“…Usefulness of PCR as an sensitive and specific diagnostic tool for the demonstration of Acanthamoeba has been proved by several studies. Vodkin et al, (12) were the first to use PCR for the genusspecific detection of Acanthamoeba targeting the 18S rDNA using the primer pair ACARNA f1383 and ACARNA r1655.…”
Section: Resultsmentioning
confidence: 99%